Comparison of the gut content of the four-lined terapon, Pelates quadrilineatus (bloch, 1790), in Talibon, Bohol, and conception, Iloilo. - Casas, Nethalie P. (2019.)
This study was conducted to investigate the dietary composition and feeding habits of the four-lined terapon Pelates quadrilineatus collected from seagrass beds in Concepcion, Iloilo and Talibon, Bohol from 2011-2012 as part of the Fisheries Ecosystem Connectivity Project under the RESTORED SEAS research Program funded by DOST. A total of 105 fish specimens were examined from two study areas, 52 from Concepcion and 53 from Talibon. The standard length and total weight of the sample were recorded for ach stomach. The prey items were grouped into broader taxonomic categories and analyzed using the frequency of occurrence (%F). The food items in the stomach covered a small variety, ranging only from various types of zooplankton. The food composition of P. quadrilineatus varied between the two study areas, which may be attributed to type of food available, feeding behavior, and ecological condition. In Concepcion, stomach contents of P. quadrilineatus included planktonic copepods such as Cyclopoid (77.82%), Harpacticoid (12.62%), and Calanoid (8.51%), whereas diet of P. quadrilineatus from Talibon included fish larvae (44.03%), Harpacticoid (23.46%), and Calanoid (5.76%). A parabolic trend was observed in both study areas, where the fish is becoming generalist feeder, but as the size increased, it becomes specialist feeder. However, the diet composition of P. quadrilineatus between the two areas has no difference, consuming mostly planktonic copepods. The results from this study provided data such as food preference of the species as well as prey diversity which are helpful for understanding the basic functioning of fish distribution patterns in the Visayan sea which is important to achieve adequate trophic models.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Four-lined Terapon -- Talibon, Bohol; Four-lined Terapon -- Talibon, Bohol; Pelates quadrilineatus (Bloch 1790)